Key issues for stakeholder engagement in the development of health and healthcare guidelines - Petkovic, Jennifer; Magwood, Olivia; Lytvyn, Lyubov; Khabsa, Joanne; Concannon, Thomas W.; Welch, Vivian; Todhunter-Brown, Alex; Palm, Marisha E.; Akl, Elie A.; Mbuagbaw, Lawrence; Arayssi, Thurayya; Avey, Marc T.; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Established in 2015, the Multi-Stakeholder Engagement (MuSE) Consortium is an international network of over 120 individuals interested in stakeholder engagement in research and guidelines. The MuSE group is developing guidance for stakeholder engagement in the development of health and healthcare guideline development. The development of this guidance has included multiple meetings with stakeholders, including patients, payers/purchasers of health services, peer review editors, policymakers, program managers, providers, principal investigators, product makers, the public, and purchasers of health services and has identified a number of key issues. These include: (1) Definitions, roles, and settings (2) Stakeholder identification and selection (3) Levels of engagement, (4) Evaluation of engagement, (5) Documentation and transparency, and (6) Conflict of interest management. In this paper, we discuss these issues and our plan to develop guidance to facilitate stakeholder engagement in all stages of the development of health and healthcare guideline development.

Plain English summary A group of international researchers, patient partners, and other stakeholders are working together to create a checklist for when and how to involve stakeholders in health guideline development. Health guidelines include clinical practice guidelines, which your healthcare provider uses to determine treatments for health conditions. While working on this checklist, the team identified key issues to work on, including: (1) Definitions, roles, and settings (2) Stakeholder identification and selection (3) Levels of engagement, (4) Evaluation of engagement, (5) Documentation and transparency, and (6) Conflict of interest management. This paper describes each issue and how the team plans to produce guidance papers to address them.